1999
DOI: 10.1007/bf02358404
|View full text |Cite
|
Sign up to set email alerts
|

In vitro shoot regeneration ofSolanum tuberosum cultivars: interactions of medium composition and leaf, leaflet, and explant position

Abstract: SummaryShoot regeneration was investigated on explants from different leaves and leaflets of three potato cultivars Posmo, Folva and Oleva. Explants were excised from glasshouse grown plants and grown for 6 days on callus induction medium with indole-3-acetic acid or 2,4-dichlorophenoxyacetic acid. Explants were then transferred to auxin free shoot regeneration medium with gibberellic acid and 6-benzyladenine or zeatin. By using the optimum combinations and concentrations of plant growth regulators and by exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Moreover, it was observed that in case of leaf explants of cultivar 'Kufri Pukhraj', incorporation of GA 3 was also essential for shoot organogenesis as no shoot organogenesis was observed in any of the combination lacking GA 3 . The requirement of GA 3 along with zeatin for shoot induction in potato has also been reported earlier (Hansen et al 1999). Although, in this study clonal and explant specific response was observed, yet the medium formulation worked out for the optimum response was effective for both the explants (leafs and internodes) and also for all the other cultivars tested, thus ascertaining the efficacy of this protocol across the explants and cultivars tested.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, it was observed that in case of leaf explants of cultivar 'Kufri Pukhraj', incorporation of GA 3 was also essential for shoot organogenesis as no shoot organogenesis was observed in any of the combination lacking GA 3 . The requirement of GA 3 along with zeatin for shoot induction in potato has also been reported earlier (Hansen et al 1999). Although, in this study clonal and explant specific response was observed, yet the medium formulation worked out for the optimum response was effective for both the explants (leafs and internodes) and also for all the other cultivars tested, thus ascertaining the efficacy of this protocol across the explants and cultivars tested.…”
Section: Discussionsupporting
confidence: 74%
“…Earlier, there are reports on shoot organogenesis in potato (Cearley and Bolyard 1997;Hansen et al 1999;Yee et al 2001) and all these studies reported a complicated two step protocol, which is a bottle neck in undertaking an efficient trait specific improvement programme of potato. Moreover, genotype specific response of potato cultivars to plant growth regulators (PGRs) has also been reported by many researchers (Khokan et al 2009;Pal et al 2011;Wheeler et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Internode of Cardinal with 4 mg L -1 NAA required minimum days (6)(7)(8). For callus initiation, 100% explants of both leaf and internode of Heera in 5 mg L -1 NAA formed callus, whereas, internode of Diamant, Heera and Cardinal with 4, 3 and 5 mg L -1 NAA respectively produced 100% compact calli.…”
Section: Resultsmentioning
confidence: 99%
“…Different explants and different combinations of growth regulators had an influence on callus induction from various Solanum tuberosum varieties [5]. Both induction and rate of callus growth were strongly influenced by genotype [6] and in vitro callus induction was greatly influenced by the type of explants and growth regulators [7]. NAA stimulated both callus induction and root formation [8].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of variation may also be either problematic or useful for horticulturists and plant breeders and may occur in high frequency during adventitious plant regeneration or long-term callus culture (Kaeppler et al, 2000). Many researchers studied how to standardize the optimum concentrations of growth regulators for regeneration of potato and consequently great progress has been made in potato callus induction and plant regeneration (Ahloowalia, 1982;Dobranszki et al, 1999;Hansen et al, 1999;Ehsanpour and Jones, 2000;Fiegert et al, 2000;Yasmin et al, 2003;Shirin et al, 2007;Khadiga et al, 2009;Khalafalla et al, 2010;Shahabud-din et al, 2011).…”
mentioning
confidence: 99%